Human norovirus interactions with histo-blood group antigens and human milk oligosaccharides - Schroten, Horst; Hanisch, Franz-Georg; Hansman, Grant S. (Journal of virology, 2016)
Human noroviruses interact with both human histo-blood group antigens (HBGAs) and human milk oligosaccharides (HMOs). The former are believed to be important for a virus infection, while the latter might act as natural decoys in the host during an infection. However, certain noroviruses are known to bind poorly to HBGAs and yet still cause infections; some interact with numerous HBGA types but are nonprevalent; and yet others bind HBGAs and seem to be increasing in prevalence. HBGAs and HMOs can be found as soluble antigens in humans, can be structurally alike, and can interact with equivalent residues at identical binding pockets on the capsid. In this Gem, we discuss HBGA and HMO binding studies for human noroviruses, concentrating on the clinically important genogroup II noroviruses. In short, the roles of HBGA and HMO interactions in norovirus infections are still unclear.
Gesehen am 10.07.2019